PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2019 – 2021) - Vania Yuliana Indarto; Agus Purwanto (Diponegoro Journal of Accounting, 2023)
This research aims to analyze and obtain empirical evidence on the influence of financial performance, consisting of financial leverage, financial distress, earning management, and dividend policy on firm value in manufacturing companies listed on the Indonesia Stock Exchange with good corporate governance as a moderating variable during the period 2019-2021.This study utilizes secondary data with a population size of 195 manufacturing companies listed on the Indonesia Stock Exchange during the period of 2019-2021. The sampling method used in this research is purposive sampling, where the sample consists of 38 manufacturing companies based on researcher-defined criteria. The analysis method employed in this research is moderated regression analysis (MRA).The results of this study indicate that financial leverage has a positive effect on firm value, financial distress has a negative effect on firm value, earning management does not have a significant effect on firm value, and dividend policy has a positive effect on firm value. However, good corporate governance represented by independent commissioners does not moderate the relationships between financial leverage and firm value, financial distress and firm value, earning management and firm value, and dividend policy and firm value.